Ketohydrazone complexes as potential emitting material in OLED - Bahari, Haznita Rose; Garif, Mohd. Nordin; Shamsuddin, Mustaffa (The Malaysian Analytical Sciences Society (ANALIS), 2008)
Abstract Ketohydrazone is a molecule that is able to act as a bidentate ligand through the O of C=O and N of N=C in the molecule. Three ketohydrazone ligands had been fully synthesized through the condensation reaction between 2- hydroxynaphthaldehydes with various hydrazides: salisylic hydrazide, benzyhydrazide and 2-furoic acid hydrazide in a 1:1 stoichiometry. The ligands had been characterized using infrared, 1HNMR and ultraviolet-visible spectrometer. Complexation reaction between all ligands and metals, with a stoichiometry of 1:2 for Zn (II) : ligand and 1:3 for Al(III) : ligand were carried out. All six complexes obtained were characterized using FTIR and UV-Vis spectrometer. The fluorescence properties of each ligands and complexes were investigated using luminescence spectrofluorometer excited at 406 nm. It was found that the compounds emitted blue light at ? max = 470 nm. Results showed that all the ligands and molecules synthesized have the fluorescence properties and complexation with metal enhanced the intensity of the fluorescence. It was observed that complex of Al(NDB)3 showed the best potential as an emitting material for OLED as it has the highest fluorescence intensity compared to others. Abstrak Ketohidrazon merupakan sebatian molekul yang berupaya berfungsi sebagai ligan bidentat melalui O daripada C=O dan N daripada N=C di dalam molekulnya. Tiga ligan ketohidrazon telah berjaya disintesis melalui proses kondensasi antara 2- hidroksinaftaldehida dan beberapa kumpulan hidrazida, salisilik hidrazida,, 2-furoik hidrazida, dan benzihidrazida.mengikut nisbah stoikiometri 1 : 1. Semua ligan yang telah disintesis dicirikan melalui spektroskopi IR, UV-Vis dan 1H-RMN. Tindak balas pengkompleksan antara ligan yang telah disintesis dengan dua logam yang berasingan, iaitu aluminium dan zink telah dijalankan dengan nisbah ion ligam : ligan 1 : 3 bagi pengkompleksan dengan aluminium dan 1 : 2 bagi pengkompleksan dengan zink. Enam kompleks yang terhasil dicirikan melalui spektroskopi IR dan UV-Vis. Ciri-ciri pendarfluor bagi tindak balas pengkompleksan dan ligan yang terhasil telah dikaji menggunakan spektrometer pendarfluor pada panjang gelombang pemancaran 405nm. Didapati sebatian-sebatian tersebut memancarkan cahaya biru pada ? max = 470 nm. Hasil yang diperolehi menunjukkan bahawa semua ligan dan kompleks yang disintesis menunjukkan sifat pendarfluor dan pengkompleksan dengan logam dapat meningkatkan keamatan pendarfluornya.. Kompleks Al(NDB)3 menunjukkan potensi yang terbaik sebagai bahan pemancar dalam diod pemancar cahaya organik (OLED) memandangkan kompleks ini menunjukkan keamatan pendarfluor yang tertinggi.